Commitment and healing : - Isay, Richard A. (Wiley & Sons, 2006)
Richard Isay offers something far better than simple bromides and false hope. In this book, he challenges us with a provocative, illuminating, and ultimately hopeful look at ourselves and explains how those of us who yearn to love and be loved (and who doesn't?) can best find happiness and healing in a committed relationship.